The Drivers of Investment Decisions: Examining Financial Literacy, Behavior, and Income - Fitria, Rada; Wijaya, M. Rizky; Parhusip, Austin Alexander (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
The purpose of this research is to assess the effect of financial literacy, investment knowledge, financial behavior, and income on investment decisions, all of which tested using quantitative research approaches. The research's population consists of 87 samples of current Potensi Utama University students from the 2021–2024 management class. In order to gather research data, questionnaires were distributed. This research's analytical method makes use of SPSS 26. It shows that investment knowledge significanly negative, financial behavior and financial literacy significantly positive effect investment decisions but income does not effect. It is known that the adjusted r square value is 0.642 which means that up to 64.2% of the factors effecting investment decisions described by the four independent variables, with other factors outside the scope of this research explaining the remaining components.